Female teachers in the nineteenth century: Admission and evolution in the studies of Escuela Normal in the city of Cádiz - Vázquez Domínguez, Carmen (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2022)
The emergence of Escuelas Normales in the 19th century is due to a wide variety of social changes that condition the different stages through which teacher training passes in the country. This paper presents an analysis of female enrollment in this training institution in the city of Cádiz. A longitudinal tour of the registered women and the registration models is carried out, contextualizing, without entering into a prolix analysis of the legislation, of the changes in mentality and fundamental regulations that facilitated the incorporation of women into teaching.